Kant über den Selbstbetrug des Bösen - Welsch, Martin (de Gruyter, 2019)
Abstract: In Kantian philosophy, the evil heart is constituted as a system of self-degrading and self-deranging freedom by the coordination of two voluntary acts: the act of establishing radical evil and the act of a voluntary lie to oneself. The consequence is a kind of “madness of freedom”, which characterises the self-deception of evil. By discussing Kantian rhetoric as an elaborate art of writing, this structure will be explored via a new approach to reading ‘On Radical Evil in Human Nature’. The result is that it is the mere possibility of a lie to oneself originating in freedom that makes it impossible to cognise whether one’s heart is good or systematically evil.